Impact Resistance of Bendable Concrete Reinforced with Grids and Containing PVA Solution - Abd Al Kareem, S.; Ahmed, I. F. (Engineering, Technology & Applied Science Research, 2021)
The development of new building materials, able of absorbing more energy is an active research area. Engineering Cementitious Composite (ECC) is a class of super-elastic fiber-reinforced cement composites characterized by high ductility and tight crack width control. The use of bendable concrete produced from Portland Limestone Cement (PLC) may lead to an interest in new concrete mixes. Impact results of bendable concrete reinforced with steel mesh and polymer fibers will provide data for the use of this concrete in areas subject to impact loading. The experimental part consisted of compressive strength and impact resistance tests along with a result comparison with unreinforced concrete. Concrete samples, with dimensions of 100×100×100mm (cubes), and 500×500×50mm (slabs), were poured and were treated at ages of 28, 56, and 90 days. The compressive strength increased by 36.11%, 45.5%, and 52.4% respectively, whereas the impact resistance for samples reinforced with steel mesh and polypropylene fibers gave superior results to the conventional mixes.